2022
DOI: 10.3389/fpsyt.2022.977538
|View full text |Cite
|
Sign up to set email alerts
|

Short-chain fatty acids in patients with schizophrenia and ultra-high risk population

Abstract: BackgroundIndividuals who experience the prodromal phase of schizophrenia (SCZ), a common and complex psychiatric disorder, are referred to as ultra-high-risk (UHR) individuals. Short-chain fatty acid (SCFA) is imperative in the microbiota-gut-brain axis and brain function. Accumulating amount of evidence shows the connections between psychiatric disorders and SCFAs. This study aims to explore the underlying roles SCFAs play in SCZ by investigating the association of alterations in SCFAs concentrations with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…Butyrate affects the effect of anti-inflammatory and intestinal mucosa repair ( Liang et al, 2021 ). Acetate can serve as an energy substance for surrounding tissues, regulate fat cell differentiation, and synthesize long-chain fatty acids, cholesterol, glutamine, β-hydroxybutyric acid, and other substances ( Peng et al, 2021 ) that are important components of SCFAs.…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate affects the effect of anti-inflammatory and intestinal mucosa repair ( Liang et al, 2021 ). Acetate can serve as an energy substance for surrounding tissues, regulate fat cell differentiation, and synthesize long-chain fatty acids, cholesterol, glutamine, β-hydroxybutyric acid, and other substances ( Peng et al, 2021 ) that are important components of SCFAs.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent clinical study showed that alterations in concentrations of SCFAs can be linked to the pathogenesis and the cognitive impairment of schizophrenia. Additionally, a significantly lower concentration of valeric acid was reported in schizophrenia patients compared to healthy controls [83]. According to the "membrane hypothesis of schizophrenia", the abnormal production of SCFAs occurring by the altered composition of the gut microbiome may result in the activation of microglia and then disrupt cell membrane metabolism [84].…”
Section: Microbiome-gut-brain Axis Influence On Brain Functions Media...mentioning
confidence: 99%
“…Especially noteworthy within the context of schizophrenia are short-chain fa y acids (SCFAs), which are metabolic byproducts produced by gut microbes during the fermentation process [23][24][25]. SCFAs have been found to cross the blood-brain barrier and can influence CNS activity, including the modulation of microglia activity and cytokine production [26] Dysregulation of neurotransmi ers like glutamate, γ-aminobutyric acid (GABA), dopamine, and serotonin, produced by gut microbes or their precursor molecules, may also contribute to CNS disorders, including schizophrenia [27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%